Properties of a General Fuzzy Normed Space - Kider, Jehad R.; Gheeab, Manar N. (Iraqi Journal of Science, 2019)
The aim of this paper is to introduce the definition of a general fuzzy norned space as a generalization of the notion fuzzy normed space after that some illustrative examples are given then basic properties of this space are investigated and proved.For example when V and U are two general fuzzy normed spaces then the operator is a general fuzzy continuous at u V if and only if u in V implies S(u) in U.